The Role of Islamic Religious Education Teachers in Developing Students' Social and Moral Skills through an Islamic Values-based Approach at SMP Negeri 1 Nalumsari - Isa Ahlian Muttaqin; Ali, Mohamad (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Education has a crucial role as a significant learning tool and an effective means of advancing moral values and spreading social values. But that's not all: education helps build national identity, national personality and national pride. Therefore, education is a means to achieve the goal of increasing general knowledge.The significance of Islamic religious education teachers in instilling Islamic principles in the character and social competence of students is the subject of this research. Focusing on how Islamic religious education teachers help their students internalize the social and moral principles taught in Islam, this research is based on Islamic ethical principles. Using a qualitative approach, this research was conducted. Analysis of PAI lesson plans, interviews with PAI teachers, and classroom observations are part of the research process. As a result, PAI teachers help their students grow professionally by showing them practical ways to apply Islamic principles in practice. They do more than just teach; they also set a good example by acting as role models.